Ultrasonic-Assisted Synthesis of CdS/Microcrystalline Cellulose Nanocomposites With Enhanced Visible-Light-Driven Photocatalytic Degradation of MB and the Corresponding Mechanism Study - Zhu, Chaosheng; Zhang, Xiangli; Zhang, Yongcai; Li, Yunlin; Wang, Ping; Jia, Yanchi; Liu, Jin (Frontiers in Chemistry, 2022)
A simple and efficient ultrasonic-assisted approach was designed to synthesize CdS/microcrystalline cellulose (MCC) nanocomposite photocatalyst. The obtained products have been characterized by XRD, FE-SEM, TEM, UV-Vis DRS, and nitrogen adsorption isotherms. The results showed that the intimate contact of MCC and CdS is beneficial for enhancing the photocatalytic performance because heterojunction formation can efficiently promote the separation of photogenerated electrons and holes of the nanocomposite photocatalyst. By using 10% MCC coupled CdS, the decoloration rate of methylene blue (MB) in the solution under visible-light was increased nearly 50%. In addition, the reuse experiments confirmed that the CdS/MCC nanocomposite photocatalyst had outstanding cycle performance and durability. Mechanism study demonstrated that hydroxyl radicals, photogenerated holes and superoxide radicals were the active species in the photocatalytic oxidization degradation of MB.